2008
DOI: 10.2138/am.2008.2659
|View full text |Cite
|
Sign up to set email alerts
|

The parental melt of lherzolitic shergottite ALH 77005: A study of rehomogenized melt inclusions

Abstract: Lherzolitic shergottite ALH 77005 is one of the most primitive martian meteorites. To characterize the parental melt of this primitive meteorite, olivine and chromite-hosted melt inclusions have been experimentally rehomogenized. The rehomogenization was performed with hydrostatic pressures (800-1000 bars) of CO 2 + CO gas along with finely powdered graphite at temperatures of 1150-1185 °C. Equilibrium between the host and inclusion melt was determined based on the lack of zonation in the host surrounding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Experiments were run on approximately 1 mm 3 chips of each meteorite which were rehomogenized in TZM (titanium-zirconium-molybdenum) pressure vessels in sealed Pt-tubes Calvin and Rutherford 2008). Samples were enclosed in graphite powder that generates a G-CO mixture through C reaction with the oxidized sample, thereby fixing the fO 2 at low values between iron wustite (IW) and quartz-fayalitemagnetite (QFM) depending on the pressure of the experiment.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments were run on approximately 1 mm 3 chips of each meteorite which were rehomogenized in TZM (titanium-zirconium-molybdenum) pressure vessels in sealed Pt-tubes Calvin and Rutherford 2008). Samples were enclosed in graphite powder that generates a G-CO mixture through C reaction with the oxidized sample, thereby fixing the fO 2 at low values between iron wustite (IW) and quartz-fayalitemagnetite (QFM) depending on the pressure of the experiment.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Fe-Mg reequilibration in ALH 77005 olivine would potentially result in all olivine phenocrysts throughout the sample sharing the same composition (similar to that seen in high metamorphic grade chondrites). Previous studies of ALH 77005 have observed grain to grain major element compositional variations in olivine (Ikeda 1994;Calvin and Rutherford 2008) implying that major element diffusive reequilibration was not complete. As Fe-Mg diffusion is faster than REE diffusion in olivine, these results suggest that post-entrapment reequilibration of the studied melt inclusions is not significant for the REEs.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations